Sacubitril/valsartan improves ventilation stability in patients with chronic heart failure. (25th November 2020) - Sciarrone, P; Borrelli, C; Giannoni, A; Gentile, F; Aimo, A; Vergaro, G; Emdin, M; Passino, C
Abstract: Background: Sacubitril/valsartan (SV) ameliorates symptoms and prognosis in patients with heart failure and reduced ejection fraction (HFrEF), but the reasons for such effects are unclear. The impact of SV on ventilation has never been investigated. In HFrEF, apneas are highly prevalent both at daytime and nighttime and are associated with increased mortality. Purpose: We hypothesize that treatment with SV could favourably stabilize ventilation by reducing the severity of central apneas in patients with HFrEF. Methods: 51 patients with HFrEF (mean age 67±9 years, mean left ventricular ejection fraction, LVEF 27±7%) and apneas defined by an apnea-hypopnea index, AHI≥5 (median 16, interquartile range 8–28) events/hour, eligible to treatment with SV and previously on optimal medical therapy for HFrEF, were enrolled. An extensive evaluation including cardiac ultrasound and a 24-hour cardiorespiratory monitoring was performed. Results: After six months of treatment with SV, left ventricle systolic and diastolic function, mitral regurgitation (MR), left atrial volume (LAVI) and systolic pulmonary artery pressure (sPAP) were improved. Severity of apneas was reduced by 50%, 65% and 36% throughout the 24-hour, at daytime and nighttime, respectively. Conclusion: Besides its known efficacy on cardiac remodeling, SV positively decreases the apneic burden in patients with HFrEF. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Roche Diagnostics unrestricted grant